ANALISIS PERBEDAAN KINERJA KEUANGAN PADA PERUSAHAAN KOSMETIK YANG TERDAFTAR DI BEI SEBELUM DAN SETELAH MARAKNYA ONLINE SHOP - Nur Hanik Khukmiyah; Jeni Susyanti; Muhammad Agus Salim (UNIVERSITAS ISLAM MALANG, 2018)
ABSTRACT ANALYSIS OF FINANCIAL PERFORMANCE DIFFERENCE IN COSMETIC COMPANIES LISTED IN BEI BEFORE AND AFTER ONLINE SHOP This study aims to examine the differences in financial performance of cosmetics companies listed on BEI before and after the rise of online shop based on current ratio (CR), return on assets (ROA), return on equity (ROE), debt to total assets (DAR) . The population in this study all cosmetics companies listed on the BEI a number of 6 companies. The sampling technique was done by using purposive sampling method and obtained amounted to 4 cosmetics companies listed in BEI 2011-2014. The data used in this study is secondary data obtained from the financial statements of cosmetics companies listed on the BEI and this type of research belongs to comparative research. Data analysis method in this research use paired sample ttest. The results of this study show that partially return on assets (ROA) there is a significant difference to the financial performance of cosmetic companies before and after the ramp of online shop, current ratio (CR), return on equity (ROE), debt to total assets (DAR) there are significant differences to cosmetics companies listed on Indonesia Stock Exchange before and after the rise of online shop.Keywords: Financial Performance, Cosmetic Company, Online Shop.